Pengaruh rehabilitasi paru terhadap MVV dan VEP1 terhadap pasien penyakit paru obstruktif kronik stabil di RSUP H. Adam Malik Medan - Fatma Hani Lubis; Pandiaman Pandia; Amira P Tarigan (Fakultas Kedokteran USU, 2014)
Introduction : In COPD patient, need to lung function examination and measurement ventilatory muscle strength. MVV recommended as a test more spesific to measure ventilatory muscle fatigue, lung and chest mechanically capacity. MVV is a maximal air breathing exhaled in a period during hardly and fastly breathing. The aim of this study is to assess effect of pulmonary rehabilitation program in copd patient to MVV and FEV1 value before and after pulmonary rehabilitation.Method : This study as clinical trial with pretest and post test design during 12 weeks from october 2013 until december 2013 as many as 14 persons. Spirometry examination doing in these patients with MVV and FVC manouver and also pulmonary rehabilitation.Results : There is no difference in FEV1 value but increasing MVV value although not significant based on statistic. Mean of MVV value before rehabilitation is 37.379 (SD 17.1296) and after rehabilitation is 38.229 (SD 16.5461) with p= 0.849. mean of FEV1 value before rehabilitation is 45.93 (SD 21.334) and after rehabilitation is 45.21 (SD 19.510) with p= 0.768. Conclusion : Statistically there is no significant changed in FEV1 value before and after rehabilitation (p=0.768) Keywords : copd; mvv; fev128